ANALISIS PREDIKSI KEBANGKRUTAN PADA BUSN DEVISA SYARIAH YANG TERDAFTAR PADA BANK INDONESIA DENGAN MENGGUNAKAN METODE ALTMAN Z-SCORE PERIODE 2013 – 2017 - Lina Suherlianawati; Edi Wibowo; Dorothea Ririn Indriastuti (Universitas Slamet Riyadi, 2020)
Financial distressed has the meaning of funding difficulties both in terms of funds in terms of cash or in terms of working capital. The purpose of this study was to determine the financial condition of Islamic banks classified as national foreign exchange private banks. The type of data uses quantitative data. Data sources use Secondary data. The type of sample used in this study uses samples from the entire population. The number of samples used in this study were 4 Islamic banking sector companies belonging to the national foreign exchange private bank. The results showed that the Z-Score values for the 2013 - 2017 period of BNI Syariah and Bank Mandiri Syariah banks were indicated not to go bankrupt or in a healthy state where the Z-score average value of Bank BNI Syariah 6.11 and in Bank Mandiri Syariah 3,02 > 2,6. At Bank Muamalat in 2014 - 2017 and Mega Syariah Bank in 2015 - 2017 it was indicated to be unsafe or Gray Area where the value of Z-Score 1,1 < ZScore < 2,6 and the indicated bankrupt result was bank Muamalat in 2013 and the Mega Syariah bank in 2013 - 2014 where the value of Z-Score < 1,1.